Letter to Jane Tolmach from Alan Sieroty - Alan Sieroty:::::: (1968)
In an August 23, 1968 letter, Assemblyman Alan Sieroty congratulates Jane Tolmach on her election as Southern Women's Chairman of the Democratic State Central Committee.